ASUHAN KEPERAWATAN PADA NY.S DENGAN DIABETES MELITUS TIPE 2 DIRUANG PEJUANG RSUD BANGKINANG - Intan Laxmawati Intan; Ridha Hidayat (El-Emir Institute, 2025)
Cataract is a condition of cloudiness in the lens of the eye that causes decreased visual acuity. One common cause of cataracts is a long-term complication of Type 2 Diabetes Mellitus (DM). Type 2 DM is a chronic metabolic disease characterized by increased blood glucose levels due to impaired insulin secretion or insulin resistance. This case study research aims to provide nursing care for Mrs. S with Type 2 DM complicated by cataracts in the Pejuang Room of Bangkinang Hospital in 2025. The design of this study is a case study that includes assessment, nursing diagnosis, intervention, implementation, and evaluation. Data collection was carried out through interviews, observations, and physical examinations. The results of the assessment showed that Mrs. S had unstable blood glucose, impaired sensory perception (vision), and risk of injury. Interventions were carried out to help manage blood sugar levels, educate self-management, and prevent injury due to visual impairment. After three days of nursing care, the evaluation results showed that blood sugar levels were more stable, the client began to understand how to manage diabetes, and no injuries occurred during treatment. The results of this study are expected to provide information and understanding to DM patients about the importance of comprehensive disease management to prevent complications such as cataracts